Hypertension Risk Prediction Using GRU-Based Deep Learning Optimized with Stochastic Gradient Descent - Sri Murdhani, I Dewa Ayu; Randhika Kerlania, I Gusti Ayu Agung (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
Hypertension stands out as a highly common heart disease across the globe, where spotting risks early is vital to curb its prolonged effects. Still, standard check-up approaches usually hinge on unchanging health stats that overlook habit-based risk trends entirely. This gap complicates building precise alert systems for folks with different routines and body profiles. Fueled by the push for a more flexible and trend-focused strategy, the study delves into applying a Gated Recurrent Unit (GRU)-driven neural network to predict hypertension threats using lifestyle and past health data. The model blends sequential trend analysis with two GRU layers, dropout for stability, and L2 limits, tuned via Stochastic Gradient Descent (SGD) with momentum and Nesterov boosts. It lets the network uncover intricate links between factors such as age, salt consumption, stress, BMI, sleep time, family background, and treatment history. Trials on 1,985 patient records reveal solid prediction skills, with top classification rates and well-defined categories in the confusion matrix. The training and validation plots also prove smooth learning without major overfit. Next steps cover enlarging the data with continuous health metrics, incorporating attention tools for clearer insights, and pitting it against cutting-edge optimizers like AdamW and Ranger to enhance broader applicability.